2002
DOI: 10.1007/s002620100228
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of granulysin and perforin by NK cells in cancer patients and correlation of impaired granulysin expression with progression of cancer

Abstract: Granulysin has been identified as an effector molecule co-localized with perforin in the cytotoxic granules of cytotoxic T lymphocytes and natural killer (NK) cells, and has been reported to kill intracellular pathogens in infected cells in the presence of perforin and to induce a cytotoxic effect against tumor cells. The aim of the present study was to elucidate whether intracellular expression of granulysin and perforin by NK cells might be associated with progression of cancer. Flow cytometric analysis demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 0 publications
1
55
0
1
Order By: Relevance
“…It has been reported that other cytotoxic molecules that are constituted in a granule, for example granulysin, 41 can be involved in the perforin-independent CTL killing. 42 Moreover, since granzyme B can directly enter target cells by a receptor, without the involvement of perforin, the cells can be induced to undergo apoptosis by both perforin-and FasL-independent pathways. 43 Another interesting observation was that, while caspase activation was only partially required to induce 39.5-B7 lysis by perforin-mediated cytotoxicity, perforin-independent CTL lysis of 39.5-B7 cells required caspase activation to transmit death signals to the cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that other cytotoxic molecules that are constituted in a granule, for example granulysin, 41 can be involved in the perforin-independent CTL killing. 42 Moreover, since granzyme B can directly enter target cells by a receptor, without the involvement of perforin, the cells can be induced to undergo apoptosis by both perforin-and FasL-independent pathways. 43 Another interesting observation was that, while caspase activation was only partially required to induce 39.5-B7 lysis by perforin-mediated cytotoxicity, perforin-independent CTL lysis of 39.5-B7 cells required caspase activation to transmit death signals to the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Granulysin-mediated cytolysis occurs at 10 -100 M (1, 6, 23) while chemotaxis and immune cell activation occurs at much lower concentrations. Granulysin functions in innate immunity as it is released in the cytolytic granules of NK cells (5,24). In this study we show that granulysin released by CTL and NK cells in the local inflammatory environment has multiple biologic activities: in the immediate area, high concentrations of …”
Section: Discussionmentioning
confidence: 90%
“…Granulysin also kills human tumor cells, and expression of granulysin in peripheral NK cells from cancer patients has been associated with good clinical outcomes (5). Granulysin is a member of the saposin-like protein family of lipid binding proteins and colocalizes in cytolytic granules with perforin and granzymes (2).…”
mentioning
confidence: 99%
“…Granulysin has been demonstrated to possess antimicrobial effects by itself against a variety of pathogens including bacteria, fungi, and parasites [17][18][19]. In addition, granulysin is believed to contribute to anti-tumor and antiviral immune responses through its tumoricidal and antiviral activities [20,21]. It has been also reported that mRNA of granulysin is increased in the acutely rejected kidney [22].…”
Section: Introductionmentioning
confidence: 99%